WORKING WITH TEXTS IN THE 2ND-GRADE READING LITERACY COURSE - Orifjonova Hidoyatxon Foziljon qizi (Modern American Journals, 2025)
This article discusses various methods of working with texts, the importance of directly engaging with the text when analyzing literary works in primary grades, the distinctions between characters and their traits, as well as the role of integrated education.
Keywords: Primary education, reading literacy, role-play, integration.